Evaluation of Toraja (Indonesia) local aromatic rice mutant developed using heavy-ion beam irradiation - Andi Muliarni Okasa; Rinaldi Sjahril; Muhammad Riadi; Meta Mahendradatta; Tadashi Sato; Kinya Toriyama; Kotaro Ishii; Yoriko Hayashi; Tomoko Abe (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Okasa AM, Sjahril R, Riadi M, Mahendradatta M, Sato T, Toriyama K, Ishii K, Hayashi Y, Abe T. 2021. Evaluation of Toraja (Indonesia) local aromatic rice mutant developed using heavy-ion beam irradiation. Biodiversitas 22: 3474-3481. The aromatic local Toraja rice "Pare Bau" has a good grain quality and aroma. However, it has some disadvantages, including a late heading and low yield for a modern farming system. This study aims to evaluate and select early heading as well as high yield mutant lines induced by heavy-ion beam irradiation. Furthermore, dry seeds of Pare Bau were irradiated with Argon-ion (300 keV/?m) and Carbon-ion (30 keV/?m) at RI-beam factory, RIKEN Nishina Center, Japan. The germination percentages of the M1 seeds were 49% for Pare Bau irradiated with Argon-ion (PB-A), 53% for Pare Bau irradiated with Carbon-ion (PB-C), and 70% for the Control. The 13 PB-A and 13 PB-C M1 plants were selected, and the seeds were sampled in the paddy field of Hasanuddin University (20 m asl.), Makassar. During the following planting season, the M2 generation plant was examined in Enrekang District (650 m asl.), South Sulawesi, Indonesia. Based on the early heading and a larger number of panicles, the 18 PB-A and one PB-C M3 line were selected from a total of 404 M2 survival plants. The selected lines and control were grouped into seven clusters based on the quantitative phenotypic traits, indicating the existence of genetic variability. The plant yield was significantly correlated with plant height, the number of tillers, the number of panicles, as well as grain weight per panicle, which showed that these traits are good criteria for selection.